ISOLASI DAN ANALISIS KOMPONEN MINYAK ATSIRI SEREH WANGI (Cymbopogon Nardus L.rendle) MELALUI EXTRAKSI SOXHLETASI MENGGUNAKAN GAS CHROMATOGRAPHY MASS SPECTROMETRY - Erdiana Gultom; Hestina .; Salomo Sijabat (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2020)
Sereh wangi (Cymbopon nardus L. Rendle) is a plant that is spread throughout Indonesia.. Apart from being used as spices or cooking spices, this plant can be processed into more valuable by isolating the essential oils found in this plant. Isolation of essential oil from citronella plants (Cymbopon nardus L. Rendle) by soxhletation extraction method was successful. From 1000 grams of fresh fragrant lemongrass, dried, then reduced and blended to 100-120 mesh size. Of these samples used as much as 100 grams to be extracted. With the extraction process for 90 minutes using hexane as a solvent, the essential oil yield was 1.8 ml. The extracted essential oil was analyzed by Gas Chromatography Mass Spectrometry (GC-MS). From the results of GC analysis, 25 peaks were obtained in the form of chromatogram, while the spectra produced by the MS data analyzed were 10 peaks. Three of the ten highest percentages of compounds from the GC-MS data are citronellal (36.94%), octadienal (8.88%) and geranil acetate (5.75%).